Epistemologien des Umgebens Zur Geschichte, Ökologie und Biopolitik künstlicher environments - Sprenger, Florian (Edition Medienwissenschaft, 2019)
The rise of the term "environment" to describe the present marks the influence that reflection on environmental relations and the possibility of engineering artificial environments have gained since the mid-nineteenth century. In closed artificial worlds such as space stations or artificial ecosystems, the entanglement of the "environment" with the surrounding organisms becomes the subject of a biopolitics that today opens up new spaces in autonomous environmental control technologies. Florian Sprenger pursues this transformation of ecological environmental knowledge with the aim of better understanding current technologies, making the term understandable and highlighting the biopolitical dimension of each ecology.